2023
DOI: 10.3390/ijerph20031995
|View full text |Cite
|
Sign up to set email alerts
|

Kaahaajat: Finnish Attitudes towards Speeding

Abstract: People driving in excess of the posted speed limit (referred to as speeding in English or Kaahaajat in Finnish) is a common road user behaviour. In Finland, between 2000 and 2020, speeding was identified as the key contributing factor in 41% of fatal motor vehicle collisions. This may be because disregarding speed limits on motorways and on residential roads are the most common violations performed by Finnish drivers. This study identifies factors influencing speeding while driving in Finland. In particular, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…This was further supported by the fact that the percentage of speeders was significantly higher for buses/mini-buses on highways, which are typically driven by older drivers. These findings also align with previous research indicating that older drivers are more likely to speed outside built-up areas [28]. Furthermore, the results showed that males were more likely to report high non-compliance than females, which is a common finding [21,28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was further supported by the fact that the percentage of speeders was significantly higher for buses/mini-buses on highways, which are typically driven by older drivers. These findings also align with previous research indicating that older drivers are more likely to speed outside built-up areas [28]. Furthermore, the results showed that males were more likely to report high non-compliance than females, which is a common finding [21,28].…”
Section: Discussionsupporting
confidence: 90%
“…These findings also align with previous research indicating that older drivers are more likely to speed outside built-up areas [28]. Furthermore, the results showed that males were more likely to report high non-compliance than females, which is a common finding [21,28]. However, this significant association was observed only in urban areas and not on highways.…”
Section: Discussionsupporting
confidence: 90%
“…This was further supported by the fact that the percentage of speeders was significantly higher for buses/minibusses on highways, which older drivers typically drive. These findings also align with previous research indicating that older drivers are more likely to speed outside built-up areas [28,47]. This highlights the importance of considering the context of road type when examining speeding behavior.…”
Section: Discussionsupporting
confidence: 88%
“…This highlights the importance of considering the context of road type when examining speeding behavior. Furthermore, the results showed that males were more likely to report high non-compliance than females, which is a common finding [28,47]. However, this significant association was observed only in urban areas and not on highways.…”
Section: Discussionmentioning
confidence: 71%